The ghost in the system: Critical management studies in Turkey - Oba, B.; Gençer, M. (Taylor and Francis, 2016)
Critical Management Studies (CMS) did not find a place and could not establish itself in Turkish business schools. This is not a new claim; it has been argued by extant research. In an analysis of papers presented in the National Management and Organization Congress (NMOC) and examining curricula of Turkish business schools. Ozcan (2012) claims that in Turkey, management literature and management programmes have not been permeated by Critical Management Studies. Alakavuklar and Parker (2011) make similar claims; in its current forms, critical management would not find a place in Turkey due to the socio-economic realities of the country. Turkey does not have a strong tradition of anti-imperialist, civil society movements or did not experience industrial revolution. That being said, they also propose that in a developing country, local problems can be different than the ones faced by the Global North where the critical theories originated and thus, in the production of critical management, the local priorities should be taken into consideration. In an effort to explore the ideology inherited by the most popular management/organization textbooks written by Turkish academicians, Çoşkun (2009) asserts that all these textbooks strictly utilize a discourse that promotes neo-liberal ideology and neglects alternative arguments. © 2016 Christopher Grey, Isabelle Huault, Véronique Perret and Laurent Taskin.